Muslim Girl Culture and Social Control in Southeast Asia: Exploring the Hijabista and Hijabster Phenomena - Williams, James Patrick (2017)
While research on youth cultures in Southeast Asia has traditionally focused on crime, class, and delinquency among adolescent and young-adult males, the 21st century has seen an increase in research on the intersections among youth, religion, popular culture, media, identity, and consumption. As part of this trend, we report on an exploration of the terms hijabista and hijabster, which refer to female Muslim cultural identities centered on the nontraditional use of the hijab or Muslim headscarf. After situating the phenomena within the larger context of conservative regional politics and religion, we consider their cultural meanings in terms of mass and social media, suggesting that hijabista and hijabster cultures and identities are simultaneously hybrid and negotiated as young Muslim women, culture industries, and political and religious agents all employ a variety of strategies to shape emerging definitions. Finally, we reflexively discuss the implications of our own theoretical interests on interpretations of what it means to be a hijabista or hijabster.